Developing and Validating Career Sustainability Scale: Sample of Turkish University Students - Söner, Osman; Duru, Hazel; Söner, Osman (BioMed Central Ltd, 2025)
Purpose: This study aimed to develop and validate the University Students Career Sustainability Scale-Turkish Sample (US-CSS-TR) to assess university students’ perceptions of career sustainability within the Turkish context. The research sought to establish the scale’s validity and reliability while examining its relationships with job-finding anxiety, work volition, and proactive career behavior. Methods: The study followed a quantitative research design, collecting data from undergraduate students at various state and foundation universities in Istanbul. The scale development process included exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to assess structural validity. Measurement invariance tests were conducted across gender groups, and correlation network analyses were performed to examine the relationships between career sustainability and relevant career development factors. Statistical analyses were conducted using SPSS, AMOS, JASP, and JAMOVI. Results: EFA and CFA confirmed a unidimensional structure for the US-CSS-TR, demonstrating strong internal consistency and reliability (Cronbach’s alpha = 0.911 to 0.920). Measurement invariance analyses indicated that the scale was invariant across gender groups. Correlation analyses revealed that proactive career behavior had the strongest positive association with career sustainability perceptions, followed by work volition, while job-finding anxiety had a negative but non-significant relationship with career sustainability. Network analysis further highlighted the central role of proactive career behavior and work volition in shaping career sustainability perceptions. Conclusion: The study provides empirical evidence supporting the US-CSS-TR as a valid and reliable instrument for assessing career sustainability perceptions among Turkish university students. Findings suggest that proactive career behavior and work volition are key contributors to career sustainability development. The study underscores the importance of proactive career planning and adaptability in career sustainability, offering valuable insights for career counseling and educational interventions.
Keywords: Career sustainability; Measurement invariance; Scale validation; Turkish sample